Suicidal behavior and duality in disorders due to substance use among Ecuatorian drug addicts - José Alejandro Valdevila-Figueira; Omar Ruiz-Barzola; Carlos Orellana-Román; Rocío Valdevila-Santiesteban; Justo Reinaldo Fabelo-Roche; Serguei Iglesias-Moré (Revista Información Científica, 2021)
Introduction: illicit drug use is considered a favorable element highly associated to suicidal behavior. As the frequency, intensity, time of consumption and coexistence with other mental disorders, the probability of violent behavior towards oneself also increases.